Пошаговое объяснение:
Пусть длина первого отрезка -х м, тогда длина второго отрезка- 2х м,а длина третьего 2х * 3= 6х м
Составим уравнение
х+2х+6х=14
9х= 14
х=14 :9
х=1 5/9 м первый отрезок
2х= 2 * 1 5/9 = 3 1/9 м второй отрезок
6х= 6* 1 5/9= 9 1/3 м третий отрезок
Пошаговое объяснение:
Пусть длина первого отрезка -х м, тогда длина второго отрезка- 2х м,а длина третьего 2х * 3= 6х м
Составим уравнение
х+2х+6х=14
9х= 14
х=14 :9
х=1 5/9 м первый отрезок
2х= 2 * 1 5/9 = 3 1/9 м второй отрезок
6х= 6* 1 5/9= 9 1/3 м третий отрезок